To determine the power series centered at c, we may apply the formula for Taylor series:
`f(x) = sum_(n=0)^oo (f^n(c))/(n!) (x-c)^n`
or
`f(x) =f(c)+f'(c)(x-c) +(f''(c))/(2!)(x-c)^2 +(f^3(c))/(3!)(x-c)^3 +(f'^4(c))/(4!)(x-c)^4 +...`
To list the `f^n(x)` for the given function `f(x)=4/(3x+2)` centered at `c=2` , we may apply Law of Exponent: `1/x^n = x^-n` and Power rule for derivative: `d/(dx) x^n= n *x^(n-1)` .
`f(x) =4/(3x+2)`
` =4(3x+2)^(-1)`
Let `u =3x+2` then `(du)/(dx) = 3` .
`d/(dx) c*(3x+2)^n = c *d/(dx) (3x+2)^n`
`= c *(n* (3x+2)^(n-1)*3`
` = 3cn(3x+2)^(n-1)`
`f'(x) =d/(dx) 4(3x+2)^(-1)`
`=3*4*(-1) *(3x+2)^(-1-1)`
`=-12(3x+2)^(-2) or 2/(3x+2)^2`
`f^2(x) =d/(dx) -12(3x+2)^(-2)`
`=3*(-12)(-2)(3x+2)^(-2-1)`
`=72(3x+2)^(-3) or 72/(3x+2)^3`
`f^3(x) =d/(dx) 72(3x+2)^(-3)`
`=3*(72)(-3)(3x+2)^(-3-1)`
`=-648(3x+2)^(-4) or -648/(3x+2)^4`
Plug-in `x=3` for each `f^n(x)` , we get:
`f(3)=4/(3(3)+2)`
`=4/ 11`
`f'(3)=-12/(3(3)+2)^2`
`=-12/11^2`
`= -12/121`
`f^2(3)=72/(3(3)+2)^3 `
`=72/11^3`
`=72/1331`
`f^3(3)=-648/(3(3)+2)^4 `
`=-648/11^4`
`= -648/14641`
Plug-in the values on the formula for Taylor series, we get:
`4/(3x+2)= sum_(n=0)^oo (f^n(3))/(n!) (x-3)^n`
` = sum_(n=0)^oo (f^n(3))/(n!) (x-3)^n`
` =4/11+(-12/121)(x-3) +(72/1331)/(2!)(x-3)^2 +(-648/14641)/(3!)(x-3)^3 +...`
` =4/11-(12/121)(x-3) +(72/1331)/2(x-3)^2 - (648/14641)/6(x-3)^3 +...`
` =4/11-12/121(x-3) +36/1331(x-3)^2 -108/14641(x-3)^3 +...`
` = sum_(n=1)^oo 4(-3(x-3))^(n-1)/11^n`
` = sum_(n=1)^oo 4(-3(x-3))^(-1)(-3(x-3))^n/11^n`
` = sum_(n=1)^oo 4/(-3(x-3))((-3(x-3))/11)^n`
` =sum_(n=1)^oo 4/(-3x+9)((-3(x-3))/11)^n`
To determine the interval of convergence, we may apply geometric series test wherein the series `sum_(n=0)^oo a*r^n` is convergent if `|r|lt1 or -1 ltrlt 1` . If `|r|gt=1` then the geometric series diverges.
By comparing `sum_(n=1)^oo 4/(-3x+9)((-3(x-3))/11)^n` with `sum_(n=0)^oo a*r^n` , we determine: `r = (-3(x-3))/11` .
Apply the condition for convergence of geometric series: `|r|lt1` .
`|(-3(x-3))/11|lt1`
`|-1|*|(3(x-3))/11|lt1`
`1*|(3(x-3))/11|lt1`
`|(3(x-3))/11|lt1`
`|(3x-9)/11|lt1`
`-1lt(3x-9)/11lt1`
Multiply each sides by `11` :
`-1*11lt(3x-9)/11*11lt1*11`
`-11lt3x-9lt11`
Add 9 on each sides:
`-11+9lt3x-9+9lt11+9`
`-2lt3xlt20`
Divide each side by `3` :
`-2/3lt(3x)/3lt20/3`
`-2/3ltxlt20/3 `
Thus, the power series of the function `f(x) =4/(3x+2)` centered at `c=3` is `sum_(n=1)^oo 4/(-3x+9)((-3(x-3))/11)^n`
with an interval of convergence: `-2/3ltxlt20/3` .
No comments:
Post a Comment